2017
DOI: 10.1007/s10529-017-2445-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-149 promotes human osteocarcinoma progression via targeting bone morphogenetic protein 9 (BMP9)

Abstract: miR-149 promotes OS progression via targeting BMP9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Besides, miR‐346 was significantly expressed in the frontal bone versus parietal bone, and miR‐346 was reported to positively regulate osteogenic differentiation by targeting on GSK‐3β to activate Wnt/β‐catenin pathway . The identified miR‐149 in this study was also reported to target on BMP‐9 to promote OS progression . Furthermore, SMOC1 and (Tnn) were found to be involved in osteoblast differentiation, and Tnn was able to stimulate osteoblastic differentiation, and the endogenous Tnn can maintain the functional state of cultured osteoblast‐like cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Besides, miR‐346 was significantly expressed in the frontal bone versus parietal bone, and miR‐346 was reported to positively regulate osteogenic differentiation by targeting on GSK‐3β to activate Wnt/β‐catenin pathway . The identified miR‐149 in this study was also reported to target on BMP‐9 to promote OS progression . Furthermore, SMOC1 and (Tnn) were found to be involved in osteoblast differentiation, and Tnn was able to stimulate osteoblastic differentiation, and the endogenous Tnn can maintain the functional state of cultured osteoblast‐like cells.…”
Section: Discussionmentioning
confidence: 60%
“…44 The identified miR-149 in this study was also reported to target on BMP-9 to promote OS progression. 45 Furthermore, SMOC1 46,47 and (Tnn) 48 were found to be involved in osteoblast differentiation, and Tnn was able to stimulate osteoblastic differentiation, and the endogenous Tnn can maintain the functional state of cultured osteoblast-like cells. SMOC1 and Tnn were found highly expressed in the parietal bone rather than in the frontal bone.…”
Section: T a B L E 1 Predicted Target Gene Of Differentially Expressementioning
confidence: 99%
“…In contrast, overexpression of PTN also weakened the inhibitory effect of miRNA-137-3p on the proliferation of drug-resistant OS cells. MiRNA-149 is a cancer-promoting factor, 25 and its expression is significantly increased in the OS tissues. It is negatively correlated with the target gene bone morphogenetic protein 9 (BMP9) and affects the expression of Caspase3 and PARP.…”
Section: The Role Of Mirna In Adriamycin Resistancementioning
confidence: 99%
“…To our surprise, miR‐149‐3p induces apoptosis by repressing v‐akt murine thymoma viral oncogene homologue 1 (AKT1) and E2F transcription factor 1 (E2F1) expression in neuroblastoma and HeLa cells . A novel study showed that in osteocarcinoma (OS) patients, upregulation of miR‐149‐5p and the resultant downregulation of its target bone morphogenetic protein 9 (BMP9) inhibit apoptosis and then promote the progression of OS …”
Section: Mir‐149's Roles and Functions In Different Cancersmentioning
confidence: 99%